2015
DOI: 10.1002/nur.21678
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness on Cognitive Asthma Outcomes of the SHARP Academic Asthma Health Education and Counseling Program and a Non‐Academic Program

Abstract: Asthma morbidity and mortality is higher among older school-age children and early adolescents than other age groups across the lifespan. NIH recommended expanding asthma education to schools and community settings to meet cognitive outcomes that have an impact on morbidity and mortality. Guided by the acceptance of asthma model, an evidence-guided, comprehensive school-based academic health education and counseling program, Staying Healthy—Asthma Responsible & Prepared™ (SHARP), was developed. The program com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Parental knowledge of asthma and information resources are the focus of this assessment. Knowledge of asthma is defined as information pertinent to the chronic condition gained either through study or experience and focuses on topics of anatomy and pathology, symptoms and severity, stimuli to symptom exacerbation, medication treatments, and selfand family-management techniques (Kintner, 2004(Kintner, , 2007Kintner et al, 2015). Information resource(s) is defined as providers of knowledge about asthma including internet-based websites, traditional resources (e.g., journals/newspapers and professional books), and healthcare professionals (e.g., trained physicians and nurses).…”
Section: Frameworkmentioning
confidence: 99%
“…Parental knowledge of asthma and information resources are the focus of this assessment. Knowledge of asthma is defined as information pertinent to the chronic condition gained either through study or experience and focuses on topics of anatomy and pathology, symptoms and severity, stimuli to symptom exacerbation, medication treatments, and selfand family-management techniques (Kintner, 2004(Kintner, , 2007Kintner et al, 2015). Information resource(s) is defined as providers of knowledge about asthma including internet-based websites, traditional resources (e.g., journals/newspapers and professional books), and healthcare professionals (e.g., trained physicians and nurses).…”
Section: Frameworkmentioning
confidence: 99%
“…It is now estimated that over 330 million people of all ages, and all ethnic backgrounds, suffer from asthma and the burden of this disease to governments, health care systems, families, and patients is increasing worldwide (Marsden et al, 2016;GINA, 2014;Vos et al, 2013). Asthma is characterized by a major impact on the lives of affected persons resulting in missed days of school for school children, missed work days characterised by lack of productivity, unplanned childcare, emergency room visits, sleep disorders and fatigue, physical limitations and depression (Kintner et al, 2015). Asthma is a major health problem among adolescents.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…It has been suggested that education of health care providers and the public is a vital element of the response to the challenge posed by asthma (Braman, 2006;Ndiaye et al, 2004). Asthma education and prevention remains the greatest opportunity for decreasing asthma incidence and mortality (Kintner et al, 2015). Studies have also shown that health education can enhance knowledge, change attitudes and behaviours (Daboer et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, increasing the knowledge and attitudes of these groups could be expected to influence adolescents with asthma as knowledge, attitudes, and beliefs are recognised as being major determinants of health behaviour, including compliance with therapy (Brooks et al, 1993). Asthma education and prevention remains the greatest opportunity for decreasing asthma incidence, morbidity and mortality (Kintner et al, 2015). All these have been shown to improve through asthma health education intervention among school students (Valeros et al, 2001;Thies et al, 2001).…”
Section: Introductionmentioning
confidence: 99%